Pulmonary Artery Dissection Following Severe Pulmonary Artery Hypertension - Diasmada A., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Pulmonary Artery Dissection Following Severe Pulmonary Artery Hypertension